Linking Plant Functional Ecology to Island Biogeography. (April 2020) - Ottaviani, Gianluigi; Keppel, Gunnar; Götzenberger, Lars; Harrison, Susan; Opedal, Øystein H.; Conti, Luisa; Liancourt, Pierre; Klimešová, Jitka; Silveira, Fernando A.O.; Jiménez-Alfaro, Borja; Negoita, Luka; Doležal, Jiří; et al.
Abstract : The study of insular systems has a long history in ecology and biogeography. Island plants often differ remarkably from their noninsular counterparts, constituting excellent models for exploring eco-evolutionary processes. Trait-based approaches can help to answer important questions in island biogeography, yet plant trait patterns on islands remain understudied. We discuss three key hypotheses linking functional ecology to island biogeography: (i) plants in insular systems are characterized by distinct functional trait syndromes (compared with noninsular environments); (ii) these syndromes differ between true islands and terrestrial habitat islands; and (iii) island characteristics influence trait syndromes in a predictable manner. We are convinced that implementing trait-based comparative approaches would considerably further our understanding of plant ecology and evolution in insular systems. Highlights: Trait-based approaches may provide important insights into the dynamics of insular systems (i.e., true islands and terrestrial habitat islands) and can help to address key questions in island biogeography. However, the study of plant traits on islands is in its infancy and a robust framework tailored to island biogeography is lacking. Plants in insular systems, compared with the mainland, experience unique eco-evolutionary histories and are influenced by specific processes such as those related to isolation. These factors should be reflected in specific patterns of plant traits.